2002
DOI: 10.1177/002215540205001206
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Distribution of Laminin and Its Integrin Receptors in the Pancreas

Abstract: S U M M A R YTissue function is regulated by the extracellular microenvironment including cell basement membranes, in which laminins are a major component. Previously, we found that laminin-1 promotes differentiation and survival of pancreatic islet cells. Here we characterize the expression pattern of laminins and their integrin receptors in adult pancreas. Although they are expressed in the basement membrane of acinar cells and duct epithelium, no laminin chains examined were detected extracellularly in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 29 publications
7
81
1
Order By: Relevance
“…α5 Lms and Lu in mouse islets of Langerhans Our results on human tissues differ distinctly from earlier mouse studies, which have shown a single-layered Lm α5-containing BM in the vessels of islets [11,13] and lack of a Lm-511-containing BM in exocrine acini [12]. We therefore reinvestigated the Lm content of mouse islets of Langerhans using two independent new polyclonal antibodies against defined recombinant domains of mouse Lm α5 chain, domains αV and αVI [31].…”
Section: Resultscontrasting
confidence: 88%
See 1 more Smart Citation
“…α5 Lms and Lu in mouse islets of Langerhans Our results on human tissues differ distinctly from earlier mouse studies, which have shown a single-layered Lm α5-containing BM in the vessels of islets [11,13] and lack of a Lm-511-containing BM in exocrine acini [12]. We therefore reinvestigated the Lm content of mouse islets of Langerhans using two independent new polyclonal antibodies against defined recombinant domains of mouse Lm α5 chain, domains αV and αVI [31].…”
Section: Resultscontrasting
confidence: 88%
“…Numerous studies have suggested that BMs of most glandular organs contain Lm-332 and Lm-511, but both of these Lms are lacking in BMs of mouse pancreas, which only contain Lm-211 and Lm-411 [11,12]. Both these studies and a recent study [13], the subject of which has been reviewed [14], suggest that the only BM found in the mouse islets is that surrounding the vascular endothelium.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that basement membrane structure and major extracellular matrix proteins are not found between islet cells (11,38,39). Within the islet, basement membrane was observed only around capillaries (21).…”
Section: Discussionmentioning
confidence: 94%
“…In the pancreas, laminin is the major component (80%) of the basement membranes that form the interface between epithelia and connective tissues (10,11), whereas fibronectin is mainly observed underneath endothelial cells and epithelial ducts (12). Both laminin and fibronectin have been shown to affect differentiation and proliferation of ␤-cells (13)(14)(15).…”
mentioning
confidence: 99%
“…In the present investigation we sought to determine whether appropriate glucose signalling and insulin secretion could be restored in culture by re-establishing cellular interactions between islets and non-endocrine components of the human pancreas. Specifically, we aimed to re-introduce the influences exerted by pancreatic ductal epithelial cells (DECs), which are considered to be a potential source of trophic factors [19], ECM components [20] and beta cell progenitors [21] thought to contribute to sustained graft survival following islet transplantation [22].…”
Section: Introductionmentioning
confidence: 99%